The predictive role of electrocardiographic abnormalities in ischemic stroke patients with intravenous thrombolysis - Wu, Fei (Int J Cardiol Heart Vessel, 2014)
BACKGROUND/OBJECTIVES: The association between electrocardiographic abnormalities and the outcomes in acute ischemic stroke patients after intravenous thrombolysis remains unclear. We sought to assess the predictive value of electrocardiographic abnormalities in stroke patients after thrombolysis. METHODS: Consecutive acute stroke patients with thrombolysis from Feb 2008 to Jun 2013 were included. Electrocardiographic abnormalities during hospitalization were retrospectively reviewed. Outcomes were 90-day modified Rankin's Score. Multivariate logistic regression was used to analyze the association of electrocardiographic abnormalities with 90-day outcome. RESULTS: From Feb 2008 to Jun 2013, 95 acute stroke patients (median age of 67 and 64.2% male) with electrocardiographic before/after thrombolysis and 90 day modified Rankin's Score were recruited in our study. Increased age (p = 0.027), higher baseline National Institutes of Health Stroke Scale (p < 0.001) and T-wave changes (p = 0.030) were significantly associated with worse functional outcome. T-wave changes (odds ratio 5.54, 95% confidence interval 1.37–22.37, p = 0.016) were independently associated with unfavorable outcome. CONCLUSIONS: T-wave changes can be useful markers to predict the outcome in stroke patients after thrombolysis.